Studi Konsumsi Bahan Bakar Mesin Gokart 150cc dengan Variasi Nilai Oktan Bahan Bakar - Abel Fuadi; Agung Sudrajad; Imron Rosyadi (JURNAL MECHANICAL, 2021)
Petrol fuel is a very inexpendable resource of energy to move or operate a machine to work as it could be. There were so many kinds of fuel such as pertamax, pertamax turbo, and avgas, with each other has a different octane number. Fuel consumption is affected by so many factor, few between them arethe difference between their octane number. The purpose of this study is to found the consumption value of 150cc gokart engine with an octane number variant. This experiment test the specific fuel consumption and air fuel ratio of the engine mentioned above when using different fuel like pertamax, pertamax turbo, and avgas, as all of them tested using dynotest, which connected to computer to track their power value of each fuel used linearly with Rpm increase, idle Rpm, 3000, 5000, 7000 and 9000 Rpm. For specific fuel consumption count based on time needed to emptying each of the fuel tested. From the research, found that specific fuel consumption value was 680 gram/Kwh for pertamax fuel, 357 gram/Kwh for pertamax turbo fuel, and 675 gram/Kwh for avgas. In this research, the factor that affects the specific fuel consumption is the difference between octane number of each fuel type